Application of global navigation satellite systems and synthetic aperture radar technology in environmental and earth surface stability research: a reviews - Rokas Bražiūnas; Jūratė Sužiedelytė Visockienė (Mokslas: Lietuvos Ateitis)
Environmental monitoring technologies have advanced, offering reliable data to assess and mitigate the impacts of climate and ecosystem changes on the planet. Global Navigation Satellite Systems (GNSS) and Synthetic Aperture Radar (SAR) technology have contributed to this progress. The combined use of GNSS and SAR enriches environmental assessments, supporting programs for climate monitoring, water cycle analysis, and vegetation mapping. This integration is also crucial for tracking the movement of Earth’s tectonic plates and monitoring its stability, with GNSS measuring precise surface displacements and SAR providing detailed images of ground deformation. Several models and systems have been developed for large-scale global area monitoring, where GNSS and SAR data provide accurate measurements used to evaluate various parameters such as soil moisture, vegetation cover, glacier melting, and more. GNSS and SAR are widely used in monitoring tectonic plate shifts and Earth’s stability. A study conducted by the European Earth Movement Monitoring Service in the Kirkilai sinkhole area, covering 5.9 hectares, found that the system uses only four measurement points in such an area, which does not fully describe the situation of height changes over time. Therefore, it would be beneficial to create a local model or system for monitoring the Lithuanian territory using the same GNSS and SAR technologies.